A study of Australian and Chinese accountants' attitudes towards independence issues and the impact on ethical judgements - Fan, Ying; Woodbine, Gordon; Cheng, W. (Emerald Group Publishing Limited, 2013)
Purpose – The purpose of this paper is to further extend research (Fan et al., 2012a) examining the attitudes of Chinese certified public accountants with respect to independence aspects of their professional codes of conduct and their influence on ethical judgement. These attitudes are compared with those of Australian public accountants. Particular attention is given to refining a pre-existing instrument to determine measurement invariance. Design/methodology/approach – A field survey of 81 Australian and 516 Chinese public accountants was conducted including the distribution of a questionnaire. Statistical analysis included confirmatory factor analysis and measurement invariance. Findings – An analysis of data established the existence of a stable model for identifying the dimensions of independence of mind and independence in appearance within the context of the codes of conduct relevant to both cultures. Chinese accountants demonstrated significantly less concern about audit-client relationships affecting independence in appearance compared to their Australian counterparts. Interestingly, independence of mind was found to positively influence ethical judgement for both groups taken together, although Chinese accountants were the significant contributors to this model outcome.Research limitations/implications – The relatively small sample of Australian accountants drawn from a limited population base could influence the quality of data analysis. This paper provides a further research direction for re-examining the relationship between Australian public accountants’ attitudes towards their code of professional ethics and their ethical judgements in a significantly larger sample. Practical implications – This paper is particularly useful to the profession in that it will provide members with better insights into how accountants in different cultural settings view audit independence issues and their relationships with audit clients. Second, this study offers a scale for measuring attitudes towards codes of professional ethics for further cross-cultural studies. Originality/value – An exploratory research exercise that indicates that accounting practitioners in divergent cultures demonstrate similar concerns about independence issues, although it is believed that guanxi is likely to explain why Chinese accountants are less concerned with independence of appearance issues. The research also presents a validated instrument for examining attitudes towards codes of ethics.